ZNF830 mediates cancer chemoresistance through promoting homologous-recombination repair. Issue 3 (13th December 2017) - Chen, Guo; Chen, Jianxiang; Qiao, Yiting; Shi, Yaru; Liu, Wei; Zeng, Qi; Xie, Hui; Shi, Xiaorui; Sun, Youwei; Liu, Xu; Li, Tongyu; Zhou, Liqian; et al.
Abstract: Homologous recombination (HR), which mediates the repair of DNA double-strand breaks (DSB), is crucial for maintaining genomic integrity and enhancing survival in response to chemotherapy and radiotherapy in human cancers. However, the mechanisms of HR repair in treatment resistance for the improvement of cancer therapy remains unclear. Here, we report that the zinc finger protein 830 (ZNF830) promotes HR repair and the survival of cancer cells in response to DNA damage. Mechanistically, ZNF830 directly participates in DNA end resection via interacting with CtIP and regulating CtIP recruitment to DNA damage sites. Moreover, the recruitment of ZNF830 at DNA damage sites is dependent on its phosphorylation at serine 362 by ATR. ZNF830 directly and preferentially binds to double-strand DNA with its 3′ or 5′ overhang through the Zinc finger (Znf) domain, facilitating HR repair and maintaining genome stability. Thus, our study identified a novel function of ZNF830 as a HR repair regulator in DNA end resection, conferring the chemoresistance to genotoxic therapy for cancers those that overexpress ZNF830.